2021
DOI: 10.1002/dneu.22815
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oxytocin on neurite outgrowth and synaptic proteins in Magel2‐deficient mice

Abstract: 012 345 16 ÿ 189ÿ 032 9 ÿ 85 16 ÿ ÿ ÿ ÿÿ ÿ ÿ ÿ ÿ ÿ ÿ ÿ ÿ ÿ ÿÿ!" ÿ ÿ #$ %ÿ& ' " ÿ( )* +* * , ÿ-../0 ÿÿ ÿ1 2ÿ '' "ÿ ÿ3 4ÿ ÿ 52 '$ ÿ66, ÿ67-7ÿ( 67-78 /98 1!, ÿ:;0 * ÿ1<2 ' ÿ2 " ÿ ÿ22 4ÿ$%ÿ ÿ " ÿ 1 ÿ '' ÿ = " ÿ ÿ ' ÿ " ÿ ÿ ÿ ÿ * ÿ >-9? 7@@? -.ÿ 'ÿ ÿ A ÿ " %ÿ ÿ &= * ÿ Bÿ ' ÿ= 2? "ÿ ' ÿ( 9? @ÿ ' 8 =0 * ÿ & ÿ " ÿ ÿ 'ÿ ÿ ' ' Cÿ ÿ '$ ÿ ÿ ' " ÿ " *Dÿ 4 'ÿ ÿ = %ÿ ÿ ÿ %" " ÿ ÿ ÿ C%=" E'8 ? 2 ÿFGHIJ K L MNO NFPQ ÿ' ÿ( ÿ ÿ ÿ " " ÿ<2 " " ÿ ÿ ÿ' ÿ ÿ ÿFGHIJ Kÿÿ ÿ2 ÿ ÿ " ÿ ÿ ( CCÿ Rÿ " , ÿ 67-90 , ÿ ÿ " ÿ ÿ FGHIJ K L MNO NFPQ ÿ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…171 The effects of oxytocin on glutamatergic system in the hippocampus. 159 and in the prefrontal cortex 172 have also been shown. Neurogenetic actions by oxytocin may also be involved in the long-lasting actions of early-life oxytocin.…”
Section: Long-term Effects Of Oxytocin Stimulation On the Brainmentioning
confidence: 80%
See 1 more Smart Citation
“…171 The effects of oxytocin on glutamatergic system in the hippocampus. 159 and in the prefrontal cortex 172 have also been shown. Neurogenetic actions by oxytocin may also be involved in the long-lasting actions of early-life oxytocin.…”
Section: Long-term Effects Of Oxytocin Stimulation On the Brainmentioning
confidence: 80%
“…Postnatal daily administration of oxytocin (2 µg day -1 in the first 2 days or postnatal week) has been shown to increase pre-or post-synaptic transcript levels of neurexins and neuroligins 159 and to prevent deficits in social behaviour and learning abilities in adult Magel2-deficient mice, a mice model of Prader-Willi syndrome and autism spectrum disorder. 160 Intranasal oxytocin administration (200 µg kg -1 ) during postnatal days 7-21 has also been shown to restore the number of hypothalamic oxytocin neurons and to reverse social deficits in contactin-associated protein-like 2 (CNTNAP2)deficient mice, another model of autism spectrum disorder.…”
Section: Postnatal Oxytocin Stimulationmentioning
confidence: 99%
“…Rodents with MAGEL2 mutations provide an animal model through which PWS can be investigated. These animals exhibit a reduction in both hypothalamic oxytocin neurons and oxytocin receptors in brain areas involved in learning (e.g., the lateral septum) as well as abnormalities in oxytocin neuronal activity [ 250 , 252 , 253 , 254 ]. Moreover, MAGEL2 knockout mice show additional disrupted arcuate nucleus hypothalamic circuits, including a reduction in POMC-positive cells and α-MSH hormone axons which are critical to induce satiety [ 255 ].…”
Section: Interventional Studies Of Oxytocin Administration In Humansmentioning
confidence: 99%
“…Although Prader-Willi syndrome is a multigene neurodevelopmental disorder with various physiological and behavioural deficits, the clinical characteristics include severe hypotonia, a newborn's poor feeding due to reduced suckling reflexes, childhood-onset obesity, lower cognitive functioning and autistic symptoms [83]. Magel2-deficient mice manifest altered gene and protein expression of PSD-95 in early brain developmental stages [5]. Magel2-deficient mice have shown altered levels of oxytocin in the hypothalamus, as well as 50% neonatal mortality due to suckling problems [84].…”
Section: Magel2 Genementioning
confidence: 99%
“…For instance, abnormal patterns of cell-adhesion molecules and scaffolding proteins, in association with altered neuronal morphology, have been observed in the "SH3 domain and ankyrin repeat containing protein 3" (Shank3) deficient mouse model [4]. Moreover, it has recently been demonstrated that altered expression of specific genes are involved in processes of neurite elongation and synapse formation in the early developmental periods of MAGE Family Member L2 (Magel2)-deficient mice [5], which is another model known for the presence of autismlike symptoms. Currently, it appears that crucial factors that play a role in the pathogenesis of autism are defects and abnormalities found in postsynaptic density proteins [6][7][8].…”
Section: Introductionmentioning
confidence: 99%